A JOURNEY TO INDIVIDUATION: JUNGIAN ARCHETYPES AS EXPERIENCED BY JIN KAZAMA IN TEKKEN 8 - Rahmansyah, Noor Rizky (Universitas Negeri Surabaya, 2025)
This study explores the character development of Jin Kazama in Tekken 8 as a narrative representation of Carl Gustav Jung’s theory of individuation. Utilizing a qualitative textual analysis, the research examines key narrative moments, character interactions, and symbolic visual design from the game’s story mode. The analysis focuses on Jungian archetypes—such as the Shadow, the Anima, the Wise Old Man, and the Self—to trace Jin’s psychological transformation. The findings reveal that Jin’s internal conflict with the Devil Gene symbolizes his confrontation with the Shadow, while his emotional encounter with his mother, Jun Kazama, reflects the integration of the Anima. Guidance from the character Leroy Smith further illustrates the influence of the Wise Old Man archetype, culminating in Jin’s integration of the Self, represented visually by his dual wings. Through this lens, Tekken 8 becomes a rich modern allegory of self-discovery and psychological wholeness, demonstrating how video games can portray complex theoretical concepts in an accessible and emotionally engaging form.